Altered interoceptive awareness in anorexia nervosa: Effects of meal anticipation, consumption and bodily arousal. Issue 7 (24th February 2015) - Khalsa, Sahib S.; Craske, Michelle G.; Li, Wei; Vangala, Sitaram; Strober, Michael; Feusner, Jamie D.
ABSTRACT Objective Impaired interoceptive awareness (IA), the subjective perception of internal body sensations, has been proposed as a vulnerability or maintaining factor in anorexia nervosa (AN). We examined whether IA of heartbeat and breathing sensations was impaired in AN across a range of arousal levels, and whether it was influenced by meal anticipation and consumption. Method: IA was assessed using randomized, double‐blinded, bolus intravenous infusions of isoproterenol, a peripheral beta‐adrenergic sympathetic agonist, and saline. Fifteen women with AN and 15 age‐, and sex‐ matched healthy comparisons (HC) were evaluated before and after consumption of a 1, 000 Calorie meal. During each infusion participants rated their moment‐to‐moment intensity of heartbeat and breathing sensations with a dial. To measure IA we evaluated interoceptive detection thresholds, retrospective ratings of palpitation and dyspnea intensity, and interoceptive accuracy via correlations between subjective dial ratings and observed heart rate responses. Results: Contrary to prediction the AN group was more likely to report detection of interoceptive sensations across all conditions, an effect driven by false discriminations at low arousal levels. Concordant with prediction, meal anticipation was associated with intensified interoceptive sensations, particularly dyspnea. There were no differences in interoceptive accuracy. Discussion: This represents the first demonstration of interoceptive prediction errors in AN. Although IA is unimpaired at high arousal levels in AN, prediction signals are abnormal at low arousal levels, especially during meal anticipation. Altered interoceptive prediction signaling during meal anticipation could contribute to phenotypes of high anxiety in AN or alternatively, might be explained by enhanced meal associated anxiety. © 2015 Wiley Periodicals, Inc. (Int J Eat Disord 2015; 48:889–897)